Improving Teachers' Ability to Integrate TPACK in Their Lessons through Hands-on Activities: A Lesson Study Based Research - Hidayati, Istiqlaliah Nurul; Rahmah, Mursidah; Gusnadi, Gusnadi (Universitas Negeri Padang, 2022)
Pedagogy and Content Knowledge (TPACK) which is a unification between the use of technology, knowledge in the field of pedagogy and knowledge related to lesson content is currently being intensified by the government to be practiced in schools. Teachers are required to develop one more skill in their profession, namely the skill of using technology-based learning media that is in accordance with pedagogical principles and is also relevant to the lesson content. Due to the importance of integrating TPACK into learning, material on TPACK currently has its own portion in the Teacher Professional Education Program (PPG) curriculum. But what are the techniques for teaching TPACK so that teachers' skills in integrating TPACK into learning can improve? In this study, the researcher who is also the supervisor of learning practices in the PPG program directs students to prepare for learning practices using the Lesson Study. The TPACK teaching is carried out using the hands-on at the preparation stage (plan). After planning (plan), students who are selected to become model teachers will practice teaching as is done by all students, but the model teacher learning videos will be observed by other students and other students will provide input and observations during the reflection phase (see) . After three cycles of learning practice were carried out, students showed significant improvements both in learning tools and in learning practices.